Mixed-ligand manganese(II) complexes with 5-phenyltetrazole and polypyridine derivatives: Synthesis, crystal structures and biological activity - Ekaterina A. Ermakova (Elsevier, 2021)
Mixed-ligand manganese(II) complexes [Mn3(bipy)2L4(OAc)2] (1), [Mn2(dmbipy)2L2(OAc)2] (2) and [Mn(dmphen)2L2] (3), where L – 5-phenyltetrazolate anion, bipy – 2,2′-bipyridine, dmbipy – 2,2′-bi-4-picoline, dmphen – 4,7-dimethyl-1,10-phenanthroline, have been synthesized and characterized by elemental analysis, IR spectroscopy, cyclic voltammetry and powder X-ray diffraction. Single‐crystal X‐ray diffraction analysis was carried out to determine crystal structures of complexes. The UV-vis spectroscopy has been applied to show the stability of the compounds in solution. The effect of the compounds on viability of HepG2 and Hep-2 cell lines has been investigated. Complex [Mn(dmphen)2L2] was found to be the most cytotoxic with IC50 values of 5.7 ± 0.6 µM (HepG2 cells) and 8.1 ± 1.2 µM (Hep-2 cells). The antimicrobial activity of complexes and ligands has been investigated against E. coli, S. aureus, P. italicum and C. steinii. All complexes have shown protistocidal activity against C. steinii. Complexes have been found to exhibit antioxidant activity measured spectrophotometrically using ABTS•+ radical.